Fatigue Behaviour of CFRP Strengthened Reinforced Concrete Beams - James, Valontino Ruwhellon (Department of Civil Engineering, 2020)
The performance of reinforced concrete (RC) structures, such as bridges in the heavy haul industry, may be severely impacted by fatigue when subjected to repeated cyclic loading. Fatigue not only reduces load carrying capacity and serviceability limit states (SLS), but it can cause structural failure even when the components are subjected to low stress range cyclic loading. Corrosion damage exacerbates fatigue related problems as chloride induced pitting corrosion facilitates the formation and gradual propagation of cracks under cyclic loading. A common rehabilitation and retrofitting approach that involves patch repairing and fibre reinforced polymer (FRP) strengthening has proven effective to not only restore structural capacity, but also to enhance infrastructure service life. The structural repair process involves the replacement of deteriorated cover concrete with a less permeable patch repair mortar. The patch repair only restores durability of the structure; to restore or enhance structural capacity the repair process further involves bonding of FRP laminates. Particularly in the case of FRP's with a low elastic modulus, the design is often guided by serviceability limit states as opposed to ultimate limit states (ULS), resulting in an over-reinforced structural member. In addition, the reinforcement area of commercially available FRP strengthening may exceed the design requirements, especially at low levels of corrosion damage. In both the abovementioned considerations the design may result in an over-reinforced section. At the time when this researched was proposed, the effect of increasing damage extent on fatigue behaviour of over-reinforced RC beams was not clear and merited further investigation. A scientific experimental approach was developed to investigate the long-term performance of fifteen (15) full-scale 40MPa RC beams with dimensions 155x254x2000mm and ultimate capacity of 62.3kNm. Accelerated corrosion damage was induced in varied extents which included 450mm, 800mm, 1300mm and 1800mm length to a constant degree of 10% on all specimens. Specimens from each damage extent were patch repaired using SikaCrete214 and subsequently strengthened with externally bonded with SikaCarboDurS512 carbon fibre reinforced polymer (CFRP) laminates. Four-point bending monotonic loading tests were conducted on one (1) specimen from each damage extent. The results obtained from the quasi-static tests were used to determine two (2) cyclic loading stress ranges at which the remaining 2 specimens from each damage extent would be tested under. Under the 40% and 60% stress ranges four-point bending cyclic loading tests were carried out at a test frequency of 4Hz. Information was acquired on key performance indicators that included fatigue life, crack development, failure mode and stiffness degradation, where stiffness was assessed in terms of midspan deflection, composite material strains and neutral axis shift. Information on these parameters were collected using strain gauges, linear variable differential transducers (LVDT), DEMEC strain targets and digital image correlation (DIC). Ultimate failure loads under monotonic loading showed that despite having the highest degree of corrosion, the 450mm damage extent specimen had the highest failure load of 325kN. The failure load gradually reduced to 290kN as the damage extent was increased to 1800mm and the 0mm (control) specimen failed at the lowest load of 274kN. In contrast to the static behaviour, the specimen fatigue life enhanced by 106.3% as the damage extent was increased from 450mm to 1800mm. As expected, the 40% stress range tests yielded much longer fatigue lives than their 60% stress range counterparts. Furthermore, the experimentally obtained fatigue lives were compared to three fatigue life prediction models and the Helgason and Hanson model yielded the closest correlation with the experimental results. IV ABSTRACT Crack densities were found to increase with a longer fatigue life. An increase in damage extent was found to positively affect crack development and overall stiffness of the specimen during longterm fatigue testing. This finding was further substantiated by an assessment of midspan deflection, compression concrete strain and carbon fibre strain results, which all suggested a lower neutral axis and a lower stiffness reduction rate under fatigue loading as the damage extent was increased from 450mm to 1800mm. Furthermore, the tension concrete cracks propagated gradually during longer fatigue tests periods, while the tension steel and carbon fibre were comparably less affected by the resultant internal forces. Unfortunately, the neutral axis strain measurements using DEMEC targets were unable to assess the relative effect of an increase in damage extent as well as the compression concrete and carbon fibre strains were able to. During this experimental period, it was established that the laboratory layout was not conducive for carrying out the DIC process of long-term cyclic loading tests. The area in which testing took place did not adequately protect the camera against the environment and therefore required daily storage of the equipment. Regular movement of the camera for storage purposes introduced measurement inaccuracies which accumulated over longer test periods of up 20 days. However, for the short-term tests that did not require movement of the camera, the DIC process yielded favourable results. It was possible to capture the crack patterns early in the test period when the crack growth rate and development of new cracks was high using DIC. It was found that the high strain cracks coincided with the points of maximum vertical deflection (obtained through DIC) and eventual failure location of the specimen. The points of maximum deflection obtained from the DIC process were often not at midspan, which in the absence of the DIC process, would not have been possible to predict accurately. The results have shown that the specimens with the longer damage extents exhibit improved fatigue performance than their shorter counterparts. This revealed a stark contrast to their monotonic loading performance which favoured shorter damage extents. Furthermore, DIC holds potential to predict failure location more accurately than conventional approaches used for structural health monitoring (SHS).